Antibiofilm Efficacy of Black Tiger Shrimp (Penaeus monodon) Chitosan against Aggregatibacter actinomycetemcomitans and Treponema denticola (e-GiGi, 2022)
Abstract: Shrimp shell (carapace) contains chitosan which is reported to have antibacterial property against periodontal bacteria. This study aimed to determine the antibiofilm efficacy of chitosan obtained from black tiger shrimp (Penaeus monodon) against Aggregatibacter action-mycetemcomitans and Treponema denticola in vitro. The antibiofilm activity was tested using crystal violet biofilm assay with variations of chitosan concentrations, as follows: 0.2%, 0.4%, 0.6%, 0.8%, and 1%. Chlorhexidine 0.2% was used as the positive control and acetate 1% as the negative control with 3-hour-treatment period. The biofilm optical density was analyzed using microplate reader with 490 nm wavelength. Data were analyzed statistically using One Way-ANOVA with the significance level of p